Habronyx Förster (Hymenoptera: Ichneumonidae: Anomaloninae) in Peru and Ecuador: three new species, a range extension, and a new host record - Alvarado, Mabel; Grados, Juan (Zootaxa, 2015)
The ichneumonid genus Habronyx is recorded for the first time from Peru and Ecuador, and three new species are described and figured—Habronyx (Camposcopus) flavus Alvarado, new species, H. (Habronyx) nigrofasciata Alvarado, new species, and H. (H.) saqsaywaman Alvarado, new species. Hadronyx (H.) punensis is recorded for the first time in Peru. Habronyx (H.) nigrofasciata was reared from Paracles tapina (Dyar, 1913) (Erebidae: Arctiinae). In addition, the distribution of P. tapina is expanded and figures of its larvae, pupae, and adult female and male are provided.